Unequal Socioeconomic Impacts of the Java Integrated Industrial and Port Estate Special Economic Zone on Coastal Communities in Gresik - Lutfi Hakim; Auditya Purwandini Sutarto; Havy Wardana; Tomi Indarto; Anik Nur Kholifah (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
This study investigates how local communities perceive and experience the socioeconomic impacts of the Java Integrated Industrial and Port Estate (JIIPE), a flagship Special Economic Zone (SEZ) in Gresik, Indonesia. Although SEZs are intended to stimulate regional economic development, increase employment, and attract investment, their benefits often fail to reach all affected populations. Using a parallel approach that integrates structured household surveys and in-depth qualitative interviews across four directly impacted villages—Kramat, Tajungwidoro, Peganden, and Yosowilangun—this study captures community-level variations in perceptions and lived experiences. Quantitative data highlight limited long-term employment opportunities, a decline in traditional livelihoods such as farming and aquaculture, and uneven social infrastructure improvements. Qualitative findings further reveal concerns regarding weak community engagement, symbolic corporate social responsibility (CSR) programs and environmental degradation. While some respondents acknowledged improved access to transportation and economic diversification, others expressed disillusionment with unfulfilled expectations of inclusive growth. This study emphasizes the need for SEZ governance models to include transparent, participatory mechanisms and long-term capacity-building initiatives. These findings contribute to the literature on industrial development and community welfare by offering actionable policy insights to guide more inclusive and sustainable industrial transition.